2019
DOI: 10.12714/egejfas.36.4.08
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of growth performance of European catfish (Silurus glanis L) rearing in freshwater and 5 ‰ salinity in recirculating system

Abstract: European catfish (Silurus glanis L.) is a fish that has a high economic value due to its rapid growth and delicious flesh. In this study, the growth performance of European catfish was investigated in freshwater and 5‰ salinity in recirculating system. The study was carried out using fish with an average weight of 507±13.02 g and an average total length of 42.85±0.45 cm in freshwater (Y1, Y2, Y3) and 5‰ salinity of ground water (T1, T2, T3) designed as three replications for three months. Fish were fed with 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…In our study, flash moisture ranged between 77.68 ± 0.45% and 79.45 ± 0.37% in relation to feeding type. Close values for the same trait were reported by other authors [15,16,55].…”
Section: Qualitative Flesh Productionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our study, flash moisture ranged between 77.68 ± 0.45% and 79.45 ± 0.37% in relation to feeding type. Close values for the same trait were reported by other authors [15,16,55].…”
Section: Qualitative Flesh Productionsupporting
confidence: 88%
“…There were also observed fluctuations due to the activity of alteration microorganisms as well as oxidative processes that appeared on the sample surface [64,69,72]. Moreover, for the case of lipids, the literature indicates close values to those obtained in the current study [15,16]. Linhartova et al (2018) [73] indicated catfish flesh lipids contents of 4.13% in intensive rearing system samples and 2.97% in the semi-intensive system.…”
Section: Qualitative Flesh Productionsupporting
confidence: 77%
See 1 more Smart Citation